Polypyrrole-assisted oxygen electrocatalysis on perovskite oxides. Issue 2 (9th January 2017) - Lee, Dong-Gyu; Kim, Su Hwan; Joo, Se Hun; Ji, Ho-Il; Tavassol, Hadi; Jeon, Yuju; Choi, Sihyuk; Lee, Myeong-Hee; Kim, Chanseok; Kwak, Sang Kyu; Kim, Guntae; Song, Hyun-Kon
Abstract : The overpotentials of the oxygen reduction on perovskite oxide catalysts were significantly reduced simply by mixing the catalyst particles with polypyrrole/carbon composites (pPy/C). Abstract : Nitrogen-containing electrocatalysts, such as metal–nitrogen–carbon (M–N–C) composites and nitrogen-doped carbons, are known to exhibit high activities for an oxygen reduction reaction (ORR). Moreover, even if the mechanism by which nitrogen improves the activities is not completely understood, a strong electronic interaction between nitrogen and active sites has been found in these composites. Herein, we demonstrate a case in which nitrogen improves the electroactivity, but in the absence of a strong interaction with other components. The overpotentials of the ORR and oxygen evolution reaction (OER) on perovskite oxide catalysts were significantly reduced simply by mixing the catalyst particles with polypyrrole/carbon composites (pPy/C). Any strong interactions between pPy (a nitrogen-containing compound) and active sites of the catalysts are not confirmed. A scenario based on the sequential task allocation between pPy and oxide catalysts for the ORR was proposed: (1) molecular oxygen is incorporated into pPy as a form of superoxide (pPy + O2 − ), (2) the superoxide is transferred to the active sites of perovskite catalysts, and (3) the superoxide is completely reduced along the 4e ORR process.